A Novel Inorganic-Organic Hybrid Material Based on Monosubstituted Keggin-Type Polyoxometalates by a Metal-Nitrogen of Covalent Bonding - Xue, Yingxue; Guo, Xiaohong; Li, Chao; Li, Jing; Ren, Xiaozhen; Zhou, Guangdong (Asian Journal of Chemistry, 2013)
A new inorganic-organic hybrid material Na(ANIH)4ANI[PW11Ni(ANI)O39]·12H2O (ANI = aniline) was prepared based on transition-metal monosubstituted keggin type polyoxometalates [PW11Ni(H2O)O39]5- as inorganic species and aniline as organic ligand by a covalent bonding of Ni-N. The as-prepared hybrid material was characterized by elemental analysis, IR spectroscopy, TG-DTA analyses, UV-visible spectra and X-ray photoelectron spectroscopy (XPS). Elemental analysis and TG-DTA results confirm the formula of the hybrid material. Experimental results of UV-VIS, IR and XPS approve that the Ni-N covalent bond is formed between the transition-metal in the Keggin-type anion [PW11Ni(H2O)O39]5- and the nitrogen atom of ANI and the ANIH+ exists as counter ion. Moreover, photocatalytic activity of the as-prepared hybrid material was investigated by photodegradation of dye rhodamine B under UV irradiation and the results showed that the hybrid material exhibited high photocatalytic activity for treatment of dye-containing wastewater.